Beautiful Piles of Bones: An Interview with 2017 Genetics Society of America Medal Recipient David M. Kingsley. Issue 4 (30th November 2017) - Kingsley, David M
Abstract: The Genetics Society of America Medal is awarded to an individual for outstanding contributions to the field of genetics in the last 15 years. Recipients of the GSA Medal are recognized for elegant and highly meaningful contributions to modern genetics, exemplifying the ingenuity of GSA membership. The 2017 recipient is David M. Kingsley, whose work in mouse, sticklebacks, and humans has shifted paradigms about how vertebrates evolve. Kingsley first fell in love with genetics in graduate school, where he worked on receptor mediated endocytosis with Monty Krieger. In his postdoctoral training he was able to unite genetics with his first scientific love: vertebrate morphology. He joined the group of Neal Copeland and Nancy Jenkins, where he led efforts to map the classical mouse skeletal mutation short ear . Convinced that experimental genetics had a unique power to reveal the inner workings of evolution, Kingsley then established the stickleback fish as an extraordinarily productive model of quantitative trait evolution in wild species. He and his colleagues revealed many important insights, including the discoveries that major morphological differences can map to key loci with large effects, that regulatory changes in essential developmental control genes have produced advantageous new traits, and that nature has selected the same genes over and over again to drive the stickleback's skeletal evolution. Recently, Kingsley's group has been using these lessons to reveal more about how our own species evolved. This is an abridged version of the interview. The full interview is available on the Genes to Genomes blog, at genestogenomes.org/kingsley/ .